2014
DOI: 10.25011/cim.v37i5.22013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the withdrawal phase in a swine controlled intestinal donation after circulatory death model

Abstract: Purpose: Transplantation of donation after cardiac death (DCD) intestine has higher rates of organ failure and complications. Fortunately, this is less grievous in a subclass of DCD called controlled (CDCD), those with irreversible but incomplete brain injury. The aim of the paper is to establish a CDCD porcine model which is closely mimicking human CDCD scenario, and investigate the physiologic changes from withdrawal of ventilatory support to circulatory arrest. Method: Ten domestic crossbred pigs were ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One possible mechanism for this may be that, unlike brain death, organ damage during circulatory arrest is mediated by inflammatory changes (e.g. cytokines and damage‐associated molecular patterns), acidosis, and hypoxia affecting the graft prior to recovery, all processes that may take place in the peri‐withdrawal period .…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for this may be that, unlike brain death, organ damage during circulatory arrest is mediated by inflammatory changes (e.g. cytokines and damage‐associated molecular patterns), acidosis, and hypoxia affecting the graft prior to recovery, all processes that may take place in the peri‐withdrawal period .…”
Section: Discussionmentioning
confidence: 99%
“…Following WLST, the donor heart is forced to function in an increasingly hypoxic environment while attempting to maintain systemic oxygen delivery. Previous studies have suggested that this process is associated with a catecholamine‐mediated period of hyperdynamic circulation and ventricular distention that may exacerbate the severity of injury suffered by DCD hearts ; however, a systematic description of the physiologic response to WLST in the donor heart has not been previously reported. A greater understanding of this process may inform the creation of resuscitation protocols tailored specifically to the DCD heart and evaluation strategies that identify organs suitable for transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…CA was produced by intravenous injection of atracurium besilate (0.9 mg/kg, 3 × ED95, HR Co. Ltd, Jiangsu, China) and discontinuing both propofol and mechanical ventilation as previously described . The time of circulatory arrest was determined when a pulse pressure of zero, determined by arterial line, was observed after a 5‐min “no‐touch” period.…”
Section: Methodsmentioning
confidence: 99%